2021
DOI: 10.1051/0004-6361/202141078
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate-luminosity red transients: Spectrophotometric properties and connection to electron-capture supernova explosions

Abstract: We present the spectroscopic and photometric study of five intermediate-luminosity red transients (ILRTs), namely AT 2010dn, AT 2012jc, AT 2013la, AT 2013lb, and AT 2018aes. They share common observational properties and belong to a family of objects similar to the prototypical ILRT SN 2008S. These events have a rise time that is less than 15 days and absolute peak magnitudes of between −11.5 and −14.5 mag. Their pseudo-bolometric light curves peak in the range 0.5–9.0 × 1040 erg s−1 and their total radiated e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 156 publications
5
26
0
Order By: Relevance
“…Lying within the luminosity gap, ILRTs easily fulfill the condition of being low-energy explosions. Additionally, EC SNe should synthesize only few 10 −3 M of 56 Ni [112], which, again, is consistent with observational constraints obtained for ILRTs [98,100]. Finally, the progenitor star of an EC SN is expected to be a ∼9 M luminous super-Asymptotic giant branch (AGB) star, which, during its evolution, will develop a degenerate O-Ne-Mg core [107].…”
Section: Intermediate Luminosity Red Transientssupporting
confidence: 81%
See 2 more Smart Citations
“…Lying within the luminosity gap, ILRTs easily fulfill the condition of being low-energy explosions. Additionally, EC SNe should synthesize only few 10 −3 M of 56 Ni [112], which, again, is consistent with observational constraints obtained for ILRTs [98,100]. Finally, the progenitor star of an EC SN is expected to be a ∼9 M luminous super-Asymptotic giant branch (AGB) star, which, during its evolution, will develop a degenerate O-Ne-Mg core [107].…”
Section: Intermediate Luminosity Red Transientssupporting
confidence: 81%
“…Intermediate Luminosity Red Transients (ILRTs) are a class of poorly studied gap transients that sparked debate over their origin and interpretation. While some authors invoked nonterminal outbursts of post main sequence stars to explain the observed data (e.g., [96,97]), ILRTs are among the most promising candidates for being Electron Capture Supernova (EC SN) events (see, e.g., [19,[98][99][100]). Their light curves are reminiscent of classical SNe (see the left panel of Figure 5), with a single peak and a late-time linear decline in magnitudes compatible with 56 Ni decay [98][99][100].…”
Section: Intermediate Luminosity Red Transientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nomoto 1984;Ritossa et al 1996;Kitaura et al 2006;Poelarends et al 2008), although there is no consensus yet on whether we already witnessed such an explosion. Given their faintness and low synthesised 56 Ni mass, the socalled Intermediate-Luminosity Red Transients (ILRTs; Botticella et al 2009;Stritzinger et al 2020;Cai et al 2021) are considered to be among the most promising candidates. The electron-capture SN scenario, however, can potentially produce transients with different observable properties.…”
Section: Introductionmentioning
confidence: 99%
“…surveys -, in the wavelength range (near UV, optical), in the magnitudes used to count the number of flares (duty cycle, flares per hour), in the parameters used for flare identificationflare variability index(Kowalski et al 2009), flare line index(Hilton et al 2010) -, or the existing correlation with spatial distribution, spectral type or age -begin more frequent close to the Galactic plane, at later spectral types and at younger ages(Hilton et al 2010) -, makes it quite difficult to give a realistic estimation of the number of flaring objects among our final list of unidentified transients.Other (although less numerous) types of stellar objects triggering large amplitude variations are, for instance, LBVs (van Genderen 2001), FUORs(Hartmann & Kenyon 1996), RCB stars(Benson et al 1994), ILRTs(Cai et al 2021), K giants(Tang et al 2010), cataclysmic objects like novae or pulsating variables like Miras(Reid & Goldston 2002), RV Tau stars(de Ruyter et al 2005) or Cepheids…”
mentioning
confidence: 99%